Decision Support System for Determining KIP Lecturers Using the Topsis Method at STMIK Pelita Nusantara - Nera Mayana Br Tarigan; Amran Sitohang (INFOKUM, 2022)
In the selection of KIP Lecture recipients, private tertiary institutions are given flexibility in recruiting. However, in terms of selection, there are often problems, where the quotas given to applicants are very different. The ratio of applicants and quotas can exceed 10:1 and increase every year so that problems arise in determining who is entitled to receive KIP Lectures from among a large number of applicants. This study aims to overcome this problem by building a decision support system by applying the TOPSIS method. The alternatives in this study were KIP registrants studying at STMIK Pelita Nusantara and the criteria for analysis were SMA/SMK Graduation Years, Economic Limitations, Parents' Income, Number of Dependents on Parents, Home Status, Academic Achievement, Extracurricular Achievements, TPA Score. The objectives of this study are 1) How to assist the management of STMIK Pelita Nusantara in determining KIP Lecture recipients every year based on the quota provided by the government?; 2) How to apply the TOPIS method in determining KIP recipients at STMIK Pelita Nusantara?; 3) How to build a decision support system for determining KIP Lecture recipients by applying the TOPSIS method to assist the management of STMIK Pelita Nusantara every year? The stages of the research method are carried out starting from identifying problems, collecting data, analyzing with the TOPSIS method, system design, system development, system testing, and publication of scientific articles. From the results of the research conducted, it can be concluded that the TOPSIS method can be implemented in determining recipients of KIP Lectures at STMIK Pelita Nusantara